Caring for Patients with Type II Diabetes Mellitus: A Nursing Case Report - Era, D.P. (Pusat Publikasi Nusantara, 2022)
Diabetes Mellitus (DM) is a disease characterized by an insufficient amount of insulin that does not function normally. According to data of Basic Health Research of Indonesia Government year 2018, the global prevalence of DM among those aged 55 to 64 years reached 6.3% of 265 individuals, the highest value among all other age groups. To present a case study with TTDM in Samarinda, Indonesia and to determine the nursing care plan, explaining the nursing interventions and showing the importance of nursing care of patients with DM. we treated 2 patients who had TTDM using a standardized nursing process for 3 days and made observations and recorded the similarities and differences that emerged as a result of disease response and the effects of the treatment provided. Researcher has completed collecting data set which was then used to establish each of the 6 nursing diagnoses, and further each nursing plan details implemented and evaluated. There is a diversity and resemblance of data that was revealed in the discussion session of ther report. Using a thematic analysis approach, patterns in the data were identified and analyzed. The data were then synthesized using Indonesian Nursing Standardized (3S) terminology. The patient's positive health outcomes supported the accuracy of the diagnoses and the appropriateness of the nursing interventions. case study method contributes in understanding the overall nursing care for patients, especially those with TTDM because it opened up nursing scenarios that support nurses in utilized critical thinking skills including in making decisions in the use of the entire nursing process. By carefully implementing chosen interventions through nursing process nurse was able to compare data between cases, to determine the causes of differences and similarities from the data obtained and analyze based on appropriate theories and concepts.